Overview of Emotional Intelligence of Cricket Athlete - Muhammad Azim (Universitas Negeri Padang, 2019)
The problem in this study is that the level of intelligence of cricket athletes in West Sumatra is unknown, in certain sports in the cricket branch, someone who has intelligence is still not enough, but must communicate with maturity and can send it in a positive direction. This study aims to describe the level of intelligence of cricket athletes in west sumatra seen and reviewed from self-awareness, self-motivation, motivation, empathy, and social skills. The type of this research is classified into descriptive research, with the total funds of all cricket athletes in west sumatra is 20 athletes. The technique used in this study is the total sampling technique with 20 sample whereas the data analysis used a percentage technique. The results of this study show and reveal that the emotional intelligence of cricket athlete in west sumatra are self-awareness, self-motivation, motivation, empathy, and social skills at 75% then the results of this research is the cricket athletes in west sumatra do not have good emotional intelligence.